Implementing Green Marketing Strategy By Processed Food Companies – Can Sustainable Development & Csr Be Used In Marketing? (International Journal of Food and Nutritional Sciences, 2022)
Green Marketing is about the 4 Ps of marketing mix integrated with the environment. Conceptually, green marketing is discussed in various forums and at different levels. The more it is addressed the message of protecting the environment is spread among the people in the society and community. This encourages the people to bring in the practice of protecting the environment in they consumption and daily life. As the people change in their consumption, this alerts the marketers and manufactures to understand that the consumers are changing and so do their consumption choices. The marketers have to change their marketing strategies, and also ensure to bring the green concept into their marketing initiatives. Thus, the researcher aims to study the effect of the green marketing concept in processed food companies in Indian market, analyze the green marketing strategies, policies, and practices, and examine the implementation of green marketing. An exploratory study is conducted on seven well established processed-food companies indulged in protecting the environment, society, and community through CSR and SD initiatives. Findings indicate that processed food companies market their products based on product attributes such as taste, quality, and affordability. The analysis was conducted based on Porter’s Generic Competitive Strategy and Ginberg and Bloom’s Green Marketing Strategy Matrix. It is concluded that all the seven processed food companies discussed in the study are Shaded Green using differentiate strategy and indulged in sustainable and CSR activities. But these activities are not integrated in the marketing strategies to persuade the customers. There is scope to implement green marketing strategies by incorporating SD and CSR initiatives and building product brands.